2017
DOI: 10.1016/j.molmet.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation alters transcriptional rates of differentially expressed genes and contributes to pathophysiology in mice fed a high fat diet

Abstract: ObjectiveOvernutrition can alter gene expression patterns through epigenetic mechanisms that may persist through generations. However, it is less clear if overnutrition, for example a high fat diet, modifies epigenetic control of gene expression in adults, or by what molecular mechanisms, or if such mechanisms contribute to the pathology of the metabolic syndrome. Here we test the hypothesis that a high fat diet alters hepatic DNA methylation, transcription and gene expression patterns, and explore the contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…It has been observed that prolonged high-fat diet maintenance during adulthood in mice dynamically changed DNA methylation and expression of genes in fat-specific depots, such as gonadal adipose tissue 23 . In addition, a high-fat diet resulted in hyper-methylation and decreased transcription and expression of important hepatic genes controlling lipid homeostasis in a mouse model 24 . The influence of diet on global DNA methylation of PBMCs in the current study was more varied compared to telomere length, but also dependent on animal strain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that prolonged high-fat diet maintenance during adulthood in mice dynamically changed DNA methylation and expression of genes in fat-specific depots, such as gonadal adipose tissue 23 . In addition, a high-fat diet resulted in hyper-methylation and decreased transcription and expression of important hepatic genes controlling lipid homeostasis in a mouse model 24 . The influence of diet on global DNA methylation of PBMCs in the current study was more varied compared to telomere length, but also dependent on animal strain.…”
Section: Discussionmentioning
confidence: 99%
“…Increased DNA Methylation in E-Boxes in Promoter/ Enhancer Areas of Cell Cycle Genes in 1-Year-Old Mice Fed Short-term HFD An HFD has been reported to induce methylation changes in gene regulatory regions in multiple tissues, including pancreatic b-cells (45,46). Therefore, we used a targeted DNA methylation analysis (47) to investigate the DNA methylation pattern of the 21 Myc-targeting cell cycle genes identified in Fig.…”
Section: Myc Recruitment To Cell Cycle Promoters Is Enhanced In Isletmentioning
confidence: 99%
“…In fact, it has been demonstrated that a VLDL-and LDL-rich lipoprotein mix induces de novo DNA methylation in THP-1 macrophages via the activation of DNMT1 [58]. Other evidence reports that a high-fat diet promotes hypermethylation and decreases the transcription of hepatic genes controlling lipid homeostasis in a mouse model [59]. It also affects global DNA methylation in rat PBMCs and mouse heart [60,61].…”
Section: Discussionmentioning
confidence: 99%